Influence of Resin Content and Particle Size on Particleboard from Leucaena Leucocephala - Yuziah Mohd Yunus, Nor; Kasim, Jamaludin; Razali, Zulhilmi; Mohd Nazri Wan Abdul Rahman, Wan (International Journal of Engineering and Technology, 2018)
Overcoming shortage of raw material for particleboard manufacturing in Malaysia is crucial. Using fast growing forest plantation species such as Leucaena leucocephala provide a possibility. The study investigates the physical and mechanical properties of particleboard (density 700 kgm3) from Leucaena leucocephala with variables of resin content (10, 12 & 14 %). and particle size (1.0 mm, 2.0 mm & Unscreen).Â Resin used was melamine urea formaldehyde, for high moisture resistance particleboard.Â It is aimed for use at flooring and wet kitchen cabinet. Resin content influence physical and mechanical properties of particleboard with increase of resin content. Bigger particle size contributes to better mechanical properties, but higher in absorption of water. The result shows treatments passing minimum requirements of BS EN standard.Â Â